Perceptions of nurses on Systematization of Nursing Assistance in postoperative cardiac surgery (Research, Society and Development, 2019)
Care for the human being runs through its various life cycles, being integrated by work methodologies that encourage the integrality of health actions, such as the Systematization of Nursing Assistance (SAE), that assist in practices of prevention and rehabilitation of patients with Cardiovascular Diseases (CVD). The objective of this study was to analyze the perceptions of nurses about the application of Nursing Care Systematization in patients in the postoperative period of cardiac surgery. This was a qualitative, descriptive and exploratory study, carried out from January to June 2019. Data collection was performed through an interview with semistructured questions about SAE with six nurses working in the Intensive Care Unit (ICU) of a medium-sized hospital in Vale do Taquari / RS. The responses were analyzed according to the content of Bardin (2016), organized into three categories. Participants confirm that SAE is a good instrument that favors autonomy in decision making, being an important tool in the organization of patient care in the postoperative period of cardiac surgery. The study contributes to understand the importance of SAE as a tool in patient care in the postoperative period of cardiac surgery.